Influencia del pimiento rojo pulverizado como sustituto del nitrito de sodio sobre la calidad de un embutido curado “cabano” - Macay Rodríguez, Jhon Byron (2025)
The objective of this research was to evaluate the influence of powdered red pepper at different percentages as a partial substitute for nitrate on the microbiological quality of a cured cabano sausage. The methodology consisted of a completely randomized experimental design with a unifactorial arrangement, using four replicates per treatment, totaling 16 experimental units of 50 g each for the different analyses. Before analyzing the final product, the physicochemical properties of the powdered pepper were characterized, including ash content, acidity, pH, moisture, and nitrate content, which showed values consistent with those reported by other authors, except for the nitrate level. The nitrate content, determined by spectrometry, revealed a concentration of 6209.0205 mg/kg. After the cabano processing was completed, it underwent a 30-day curing period during which key parameters such as pH, residual nitrite, and microbiological quality were evaluated. The results indicated that the pH in all treatments exceeded the limits established by the NTE INEN 1338 standard; in addition, the residual nitrite values were consistent with other studies. Microbiological analyses revealed that the treatments were effective against Salmonella and E. coli but ineffective against Staphylococcus aureus.